Behavior intervention strategies for the preschool an experimental-naturalistic approach - Sayo, Teresa P.
Preschool is gaining its momentum as one of the levels of education, thus there is a need for its own guidance program. This study dealt with an aspect of this guidance program. It tested the efficacy of behavior modification strategies for changing maladaptive behaviors of children in normal preschool classes. The general objective was to bring about change in maladaptive behaviors and maintenance of learned behaviors through the systematic application of behavioral counseling techniques.